Potential adverse actions of prenatal exposure of acetaminophen to offspring - Wu, Ka; Lu, Wensheng; Yan, Xin (Frontiers in Pharmacology, 2023)
Acetaminophen (APAP) is a widely used as analgesic and antipyretic drug. APAP is also added as an active ingredient in various medications to relieve pain and reduce fever. APAP has been widely used in pregnant women in the past decades because it is considered a relatively safe drug with recommended dose in different countries. However, an increasing number of epidemiological and experimental studies have shown that APAP exposure during pregnancy may increase the risk of inducing reproductive and neurobehavior dysfunctions, hepatotoxicity in offspring. This review aims to assess the potential effects of prenatal APAP exposure on offspring growth and development.